Homologous Bromides Treatment for Improving the Open‐Circuit Voltage of Perovskite Solar Cells. Issue 6 (19th December 2021) - Li, Yong; Xu, Weidong; Mussakhanuly, Nursultan; Cho, Yongyoon; Bing, Jueming; Zheng, Jianghui; Tang, Shi; Liu, Yang; Shi, Guozheng; Liu, Zeke; Zhang, Qing; Durrant, James R.; et al.
Abstract: The power conversion efficiency (PCE) of solution‐processed organic–inorganic mixed halide perovskite solar cells has achieved rapid improvement. However, it is imperative to minimize the voltage deficit ( W oc = E g / q − V oc ) for their PCE to approach the theoretical limit. Herein, the strategy of depositing homologous bromide salts on the perovskite surface to achieve a surface and bulk passivation for the fabrication of solar cells with high open‐circuit voltage is reported. Distinct from the conclusions given by previous works, that homologous bromides such as FABr only react with PbI2 to form a large‐bandgap perovskite layer on top of the original perovskite, this work shows that the bromide also penetrates the perovskite film and passivates the perovskite in the bulk. This is confirmed by the small‐bandgap enlargement observed by absorbance and photoluminescence, and the bromide element ratio increasing in the bulk by time‐of‐flight secondary‐ion mass spectrometry and depth‐resolved X‐ray photoelectron spectroscopy. Furthermore, a clear suppression of non‐radiative recombination is confirmed by a variety of characterization methods. This work provides a simple and universal way to reduce the W oc of single‐junction perovskite solar cells and it will also shed light on developing other high‐performance optoelectronic devices, including perovskite‐based tandems and light‐emitting diodes. Abstract : Perovskite surface treatment by homologous bromide salts is investigated. It is found that bromides not only passivate surface defects but also penetrate into the perovskite providing bulk passivation. This leads to a large voltage of 1.24 V in a 1.63 eV bandgap device and an efficiency of 23.7% in a 1.56 eV bandgap device.